Electrochemical Fabrication of Porous Au Film on Ni Foam for Nitrogen Reduction to Ammonia. Issue 6 (13th January 2019) - Wang, Hongjing; Yu, Hongjie; Wang, Ziqiang; Li, Yinghao; Xu, You; Li, Xiaonian; Xue, Hairong; Wang, Liang
Abstract: Electrochemical reduction of N2 to NH3 provides an alternative strategy to replace the industrial Haber–Bosch process for facile and sustainable production of NH3 . The development of efficient electrocatalysts for the nitrogen reduction reaction (NRR) is highly desired. Herein, a micelle‐assisted electrodeposition method is presented for the direct fabrication of porous Au film on Ni foam (pAu/NF). Benefiting from its interconnected porous architectonics, the pAu/NF exhibits superior NRR performance with a high NH3 yield rate of 9.42 µg h −1 cm −2 and a superior Faradaic efficiency of 13.36% at −0.2 V versus reversible hydrogen electrode under the neutral electrolyte (0.1m Na2 SO4 ). The proposed micelle‐assisted electrodeposition strategy is highly valuable for future design of active NRR catalysts with desired compositions toward various electrocatalysis fields. Abstract : Porous Au film on Ni foam (pAu/NF) is directly fabricated by a facile micelle‐assisted electrodeposition method .Benefiting from its interconnected porous architectonics and active Au composition, the pAu/NF exhibits superior activity, selectivity, and durability for the nitrogen reduction reaction.